A influência da abertura de capital na competitividade do mercado imobiliário baiano - LEAL, Lucas Lima de Oliveira (2014)
This study aims to analyze the reasons that led the major builders and developers in southeastern Brazil to the IPO process, assess the impacts of the arrival of these companies on the competitiveness of the Bahian housing market and study the strategic response of local businesses, before a more adverse scenario. The focus of this work was to real estate construction, achieve the incorporation of enterprises and the construction of buildings. The research shows that the appropriate time in the market, characterized by high resource availability was the main reason that led companies to IPO, this finding reinforces the assumptions of the “marketing time”. Moreover, the results also show that fundraising in stock exchange, allowed the developers and builders coming from southeastern Brazil to extend their financial status, allowing them to increase their land bank and acquire competitors, guaranteeing them a higher production capacity and making the most adverse environment for the less capitalized competitors. In response to increased competitiveness, Bahian companies that did not resort to this source of funding, remaining privately held, prioritized execution of strategic alliances, both to develop new products, as for competitive advantage resulting from the expansion of financial capability from alliances.